If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 17 + -5x = 9 + 3x Solving 17 + -5x = 9 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 17 + -5x + -3x = 9 + 3x + -3x Combine like terms: -5x + -3x = -8x 17 + -8x = 9 + 3x + -3x Combine like terms: 3x + -3x = 0 17 + -8x = 9 + 0 17 + -8x = 9 Add '-17' to each side of the equation. 17 + -17 + -8x = 9 + -17 Combine like terms: 17 + -17 = 0 0 + -8x = 9 + -17 -8x = 9 + -17 Combine like terms: 9 + -17 = -8 -8x = -8 Divide each side by '-8'. x = 1 Simplifying x = 1
| 5x+9=2x+30 | | 2x^2-x+6=0 | | 4x^2-44x+96= | | 7x-1=4x-3 | | 4x+0.2=6.6 | | 5x+4-4x=12-29 | | n^2-n+4=0 | | 5x-11-4x=-5 | | p=4n-50 | | 6k^2+22k-8=0 | | (x+2)(x+5)=-2 | | 4w+12w-10=16w-10 | | (6+4)*2-7+9+18+(5+1*3)+5=688 | | 3(0.6+2n)-3.2=7.6 | | x(x-5)=x^2+3x+5 | | 4x+13x=102 | | x^4-9= | | (6+4)*2-7+9+18+(5+1*3)+5=x | | 2x^2=-9x | | 90x^2+1=6x | | 2.5d=0.4f+50 | | -72x^4-8x^3= | | 3(k+5)=-19 | | 15x^2-26x+8=0 | | x+9=-5x+9 | | 8y-4=3y+6 | | 8(x-8)+x=9(x-8)+8 | | (6+4)*2-7+9+18+(5+1*3)+5= | | 18x^2-50=0 | | 23x+5=15+3x | | 4(5c-1)-4=15c+7 | | 2t-8=3(t+5) |